Improving the Students’ Reading Comprehension Mastery by Using Canva and Word Wall Application in Grade VIII of SMP Negeri 18 Medan - Yudit Damanik; Erika Sinambela; Elena Elena Bárcena (Jurnal Pendidikan dan Pengajaran (JUPEJA), 2025)
Reading comprehension is a critical skill that influences students' academic success and overall literacy development. However, many students face challenges in understanding texts, which can affect their learning process. The reading comprehension skills of eighth-grade students at SMP Negeri 18 Medan are low. Many students struggle to understand texts due to limited vocabulary and a lack of interest in reading. This study aims to investigate the effect of Canva and Wordwall Application into the students’  reading comprehension mastery among Grade VIII students at SMP Negeri 18 Medan. The study adopts an experimental research methodology through a qualitative one-group design, focusing on class VIII-9 as the sample population. Data were collected through pre-tests and post-tests to assess students' reading comprehension development before and after using applications as learning media. The research sample consisted of 32 students, and the results indicated a significant improvement in reading comprehension scores after integrating digital applications.. The average score increased from 65 to 80, demonstrating a 25.29%.enhancement in reading comprehension mastery. Research findings reveal that the experimental group demonstrated a marked improvement in reading comprehension scores, indicating that the integration of technology in the classroom can enhance learning outcomes.  This research firmly establishes the critical role of innovative digital tools in modern educational practices and confidently presents recommendations for their broader implementation in classroom settings.